The Dark Side of Authority: Antecedents, Mechanisms, and Outcomes of Organizational Corruption - Aguilera, Ruth V. (Journal of business ethics, 2008)
Corruption poisons corporations in America and around the world, and has devastating consequences for the entire social fabric. In this article, we focus on organizational corruption, described as the abuse of authority for personal benefit, and draw on Weber’s three ideal-types of legitimate authority to develop a theoretical model to better understand the antecedents of different types of organizational corruption. Specifically, we examine the types of business misconduct that organizational leaders are likely to engage in, contingent on their legitimate authority, motives, and justifications. We conclude by suggesting managerial implications of our theoretical model and propose directions for future research.